2011
DOI: 10.54648/cola2011046
|View full text |Cite
|
Sign up to set email alerts
|

“Money for nothing”: The case law of the EU Court of Justice on the regulation of gambling

Abstract: In a series of recent judgments, the Court of Justice has developed its approach to games of chance and online gambling. It has made it clear it will not use the EU free movement of services provisions to liberalize the internal market for games of chance. Member States are given a remarkable discretion to regulate gambling services. To this end, the Court applies its standard test for restrictions very flexibly, including even an interesting moral strand, on the basis of overriding reasons in the general inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Previous research has suggested that channeling policies are justified in terms of higher levels of consumer protection, fewer criminal activities, and surplus of profits ( cf. , Van Den Bogaert and Cuyvers, 2011 ; Borch, 2022 ; Selkee et al, 2022 ). Our results partly support these findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research has suggested that channeling policies are justified in terms of higher levels of consumer protection, fewer criminal activities, and surplus of profits ( cf. , Van Den Bogaert and Cuyvers, 2011 ; Borch, 2022 ; Selkee et al, 2022 ). Our results partly support these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Channeling has different meanings across contexts, and these have translated into varying modes of implementation ( cf. Van den Bogaert and Cuyvers, 2011 ; Borch, 2022 ; Järvinen-Tassopoulos, 2022 ; Selkee et al, 2022 ). Also, the Finnish monopolistic gambling regime has been historically related to the funding of ‘good causes’ with gambling proceeds ( cf.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations